2015
DOI: 10.1212/wnl.0000000000002090
|View full text |Cite
|
Sign up to set email alerts
|

Availability, accessibility, and affordability of neurodiagnostic tests in 37 countries

Abstract: Objective: To determine the availability, accessibility, and affordability of EEG, EMG, CSF analysis, head CT, and brain MRI for neurologic disorders across countries.Methods: An online, 60-question survey was distributed to neurology practitioners in 2014 to assess the presence, wait time, and cost of each test in private and public health sectors. Data were stratified by World Bank country income group. Affordability was calculated with reference to the World Health Organization's definition of catastrophic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
89
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 103 publications
(91 citation statements)
references
References 13 publications
0
89
0
2
Order By: Relevance
“…Our results are particularly relevant to emerging economies where access to health technologies is improving but payors cannot afford all investigative tests (McLane et al, 2015). In this case, MRI not only supports the diagnosis of epilepsy but also provides etiological information in most PWE.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are particularly relevant to emerging economies where access to health technologies is improving but payors cannot afford all investigative tests (McLane et al, 2015). In this case, MRI not only supports the diagnosis of epilepsy but also provides etiological information in most PWE.…”
Section: Discussionmentioning
confidence: 99%
“…This is primarily caused by the fact that the use of traditional neuroimaging modalities (for an overview, see Friston, ) such as electroencephalography (EEG), magnetoencephalography (MEG), positron emission tomography (PET), or functional magnetic resonance imaging (fMRI) is restricted. In addition to questions of cost and accessibility (McLane et al, ) or the use of ionizing radiation (limited repeatability), these modalities also include contraindications due to electrical artefact's (Gilley et al, ; Viola, Thorne, Bleeck, Eyles, & Debener, ; Viola et al, ) or ferromagnetic components (Teissl, Kremser, Hochmair, & Hochmair‐Desoyer, ; Teissl, Kremser, Hochmair, & Hochmair‐Desoyer, ) of the implant. Thus, another reliable method for verification, which is frequently applicable, and bedside usable, is required.…”
Section: Introductionmentioning
confidence: 99%
“…In high-income countries, electroencephalography (EEG) recordings are a standard of care for the diagnosis of seizures, aiding in the diagnosis of epilepsy, the classification of seizures and spell types, and the selection of appropriate antiepileptic drugs (AEDs)2345. A recent survey6 of key respondents from 37 countries found that availability of EEG is 63% in low-income and 71% in lower middle-income countries. Waiting times are particularly long in the public sector, and only 40% of physicians from low-income countries perceive EEG as affordable6.…”
mentioning
confidence: 99%
“…A recent survey6 of key respondents from 37 countries found that availability of EEG is 63% in low-income and 71% in lower middle-income countries. Waiting times are particularly long in the public sector, and only 40% of physicians from low-income countries perceive EEG as affordable6. Barriers to EEG services include problems that are difficult for the individual patient or clinician to fix: inconsistent electricity supplies, the high cost of EEG equipment, the low numbers of skilled technologists and interpreters of EEG recordings, and the centralization of services in cities.…”
mentioning
confidence: 99%